Profile of hypospadias patients at Dr. Moewardi General Hospital Surakarta period 2015-2020 - Hariyono, Dedy C.; ., Wibisono (International Surgery Journal, 2022)
Background: Hypospadias is the second most common congenital malformation in males and the most common congenital malformation of the penis. This malformation is characterized by the anatomical position of the urinary tract opening on the ventral or anterior part of the penis. The prevalence of hypospadias in western countries around 8 of 1000 live births and is reported to increase every year. Methods: This study is a descriptive study with a retrospective cross-sectional approach. All data were retrieved from RSUD Dr. Moewardi Surakarta using hypospadias patients medical records from January 2015 – December 2020. The hypospadias case were classified into mild, moderate, and severe hypospadia based on location. The age of being diagnosed, concomitant congenital disease, surgery technique, and surgical complication were described. Results: There were 120 cases of hypospadias, consisted of 47.5% severe hypospadias, 34.9% moderate hypospadias and 17.4% mild hypospadias. Patients’ age of being diagnosed was most in the 1-5 years group (35.9%). Seventy-eight (75.7%) cases without concomitant congenital disease, 10.7% with undecensus testiculorum, 4.8% with cyanotic congenital disease, and 3.8% with cloacal. There were 68.9% cases repaired with first-stage surgical technique and 31.1% repaired with two-stage surgical technique. Most surgical complications were meatal stenosis 9%. Conclusions: Majority of hypospadias cases were severe hypospadia. Other profile like age of being diagnosed, concomitant congenital disease, surgery technique, and surgical complication were found in this study.